On the Use of the Ffowcs Williams-Hawkings Equation to Predict Far-Field Jet Noise from Large-Eddy Simulations. Issue 1 (January 2013) - Mendez, S.; Shoeybi, M.; Lele, S. K.; Moin, P.
This study presents best practices for the use of the permeable-surface Ffowcs Williams-Hawkings equations to calculate far-field sound from large-eddy simulations of high-speed turbulent jets. A parametric study of the Ffowcs Williams-Hawkings equations is performed by post-processing existing large-eddy simulations at different operating conditions gathering subsonic, supersonic, cold, isothermal, and heated jets. It is concluded that using the pressure formulations of the Ffowcs Williams-Hawkings equations yields better results than the density formulation, especially for the heated jet. In terms of surface closure, best results are obtained with closed surfaces, in conjunction with outflow disk averaging, which confirms the results obtained by Spalart and Shur in 2009. This is different from most previous studies, which recommend using open surfaces. In addition, detailed implementation information and quantified technical recommendations are presented as a guideline for post-processing large-eddy simulations for jet noise.